Measuring Women's Political Empowerment across the Globe Strategies, Challenges and Future Research (Cham : Springer International Publishing, 2018)
This volume brings together leading gender and politics scholars to assess how women's political empowerment can best be conceptualized and measured on a global scale. It argues that women's political empowerment is a fundamental process of transformation for benchmarking and understanding all political empowerment gains across the globe. Chapters improve our global understanding of women's political empowerment through cross-national comparisons, a synthesis of methodological approaches across varied levels of politics, and attention to the ways gender intersects with myriad factors in shaping women's political empowerment. This book is an indispensable resource for scholars of politics and gender, as well as being relevant to a global scholarly and policy community.
Introduction to Measuring Women's Political Empowerment across the Globe: Strategies, Challenges and Future Research; Amy C. Alexander, Catherine Bolzendahl and Farida Jalalzai -- Women's Political Empowerment through Public Opinion Research: The Citizen Perspective; Amy C. Alexander, Hilde Coffé -- The Status of Women's Empowerment Worldwide; Senem Ertan, Catalina Monroy, Juan Pablo -- Intersectionality and Women's Political Empowerment Worldwide; Melanie Hughes, Joshua Dubrow, -- Social Movements as Women's Political Empowerment: The Case for Measurement; Kathleen Fallon, Heidi Rademacher -- Women's Empowerment at the Local Level; Aksel Sündstrom, Lena Wängnerud -- Electing Women to National Legislatures; Diana Z. O'Brien, Jennifer Piscopo -- Legislatures as Gendered Organizations: Challenges and Opportunities for Women's Empowerment as Political Elites; Catherine Bolzendahl -- The Empowerment of Women in Diplomacy; Ann Towns, Anne-Kathrin Kreft, Birgitta Niklasson -- Measuring Women's Judicial Empowerment as Part of Political Empowerment; Sally J. Kenney -- Women Cabinet Ministers in Highly Visible Posts and Empowerment of Women: Are the Two Related?; Tiffany Barnes, Michelle Taylor-Robinson -- Women Heads of States and Government; Farida Jalalzai.-Conclusions and Future Directions; Amy C. Alexander, Catherine Bolzendahl, Farida Jalalzai.
Political Science and International Studies
text file PDF
Keywords: Identity politics; Democracy; Legislative bodies